Upaya Pencegahan Stunting dengan ABCDE di Kelas Ibu Hamil Puskesmas Sumurpanggang - Meyliya Qudriani; Ratih Sakti Prastiwi; Mutiarawati Mutiarawati; Intan Cristy Mayasari Rizqi; Selvia Mariza; Siti Saripah (Institut Teknologi dan Bisnis Semarang, 2025)
The first 1000 days of life are a golden period to optimize children's growth to avoid stunting. The pregnancy period plays a very important role in determining the health status of the mother and fetus. Specific nutritional intervention efforts are focused on the First 1,000 Days of Life (HPK) group, namely pregnant women, breastfeeding mothers, and children 0-23 months, because the most effective prevention of stunting is carried out in the 1,000 HPK (golden period or critical period/windows of opportunity) . The stunting rate in Tegal City has decreased from 23.9% to 16.8% in 2022. And cases of stunting in the Sumur Panggang Community Health Center area are 153 cases (9.9%) in 2023. One of the causes is malnutrition. due to the mother's lack of knowledge about providing balanced nutrition to children. So this requires intensive handling in this area. This Community Service was carried out on June 10 and 13 2024 at the Pregnant Women's Class in the Sumurpanggang Community Health Center Working Area, Tegal City. The target of this service activity is 20 pregnant women who take part in the Pregnancy Class in the Sumurpanggang Community Health Center Work Area. The method of this activity is by conducting outreach, providing material to participants about Stunting (definition, causes and impacts) and prevention using ABCDE. The activity went well and was conducive and participants were enthusiastic in presenting the material and actively asking questions. And in the evaluation there was an increase in participants' knowledge after being provided with material counseling.